Smart SIAKAD Android based using RecyclerView - Azizah Azizah; Iskandar Fitri; Fauziah Fauziah; Nur Hayati (STMIK PONTIANAK, 2020)
The Academic Information System (SIAKAD) android-based is an information system that can facilitate students and prospective students in obtaining information about the University and academics through mobile devices. The stages of study used waterfall method consisting of analysis, design, coding, testing and maintenance. This application is made using the RecyclerView method in conducting the application development of academic information systems and conducting tests such as Whitebox, blackbox, test devices and UI respondents. The results from the test of the whitebox, the total number of Cyclomatic Complex city (cc) amounted to 11, the Region of 15 and the independent Path of 11. The trial of the blacblox got the result that the app is already able to provide information to your existing needs. The tests of testing whether the function and appearance of the app is feasible to use and for a device trial it is obtained the average app access time of 45 seconds and the visual application display 100%. The others trial is conduct with respondents as many as 23 respondents by testing the application has been running well with the results 52.2% agreed, 39.1% very agreed and 8.7% disagree. Further of development can be directed to the addition of other features that don't exist yet. In addition, it can also be developed for mobile users in addition to Android operating systems such as iOS.